2020
DOI: 10.1080/13102818.2020.1718550
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization ofNACgenes in response to abiotic stress conditions inPicea wilsoniiusing transcriptome sequencing

Abstract: Picea wilsonii is widely used for a forestation and landscaping in China. However, the molecular mechanisms underlying abiotic stress tolerance in this species remain elusive. In this study, we examined the transcriptomic changes induced by drought and salt stress in 8-week-old seedlings of P. wilsonii via RNA-Seq analysis; seedlings grown under normal conditions (without abiotic stress) served as a control. Approximately 36.26 Gb of transcriptome data were obtained from the three treatments. A total of 4171 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Overexpression of PwNAC30 apparently reduced the survival rates of transgenic Arabidopsis when subjected to drought and salt treatment [29], suggesting the distinct role and multiple function of different members of the NAC family from P. wilsonii in response to abiotic stress. Here, based on the high-throughput RNA-seq of the expression profiles of P. wilsonii in the absence or presence of drought treatments [30], we identified PwNAC11 as one of the most differentially expressed genes (DEGs) on a transcriptional level, which is a homologue of Arabidopsis NAC transcription factors ANAC019 and ANAC072 (RD26). Protein multiple sequence alignment and BLAST analysis showed that the conserved N-terminal of PwNAC11 protein had a typical NAM domain and its C-terminal was comparatively variable.…”
Section: Pwnac11 Positively Regulates Drought Resistance In Transgenic Arabidopsismentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of PwNAC30 apparently reduced the survival rates of transgenic Arabidopsis when subjected to drought and salt treatment [29], suggesting the distinct role and multiple function of different members of the NAC family from P. wilsonii in response to abiotic stress. Here, based on the high-throughput RNA-seq of the expression profiles of P. wilsonii in the absence or presence of drought treatments [30], we identified PwNAC11 as one of the most differentially expressed genes (DEGs) on a transcriptional level, which is a homologue of Arabidopsis NAC transcription factors ANAC019 and ANAC072 (RD26). Protein multiple sequence alignment and BLAST analysis showed that the conserved N-terminal of PwNAC11 protein had a typical NAM domain and its C-terminal was comparatively variable.…”
Section: Pwnac11 Positively Regulates Drought Resistance In Transgenic Arabidopsismentioning
confidence: 99%
“…Previously, we identified two NAC transcription factors-PwNAC2 and PwNAC30-from P. wilsonii, which acted as positive and negative regulators in response to abiotic stress, respectively [28,29], suggesting the complexity and functional diversity of NAC TF members in coniferous forests. Here, based on the high-throughput RNA-sequencing (RNA-seq) of the expression profiles of P. wilsonii in the absence or presence of drought treatments [30], we identify PwNAC11 as one of the most differentially expressed genes (DEGs) on a transcriptional level and further elucidate the function and molecular mechanism underlying the ABA-mediated drought stress response. We found that overexpression of PwNAC11 in Arabidopsis obviously improved tolerance to drought stress by binding to the promoter of ERD1.…”
Section: Introductionmentioning
confidence: 99%
“…Based on our previous RNA-seq analysis [30], the full-length coding region of PwNAC31 was amplified from cDNA of Picea wilsonii, which had an ORF (open reading frame) with 975 bp. Its corresponding protein contained 324 amino acids.…”
Section: Identification and Analysis Of Pwnac31mentioning
confidence: 99%
“…Therefore, it is necessary to uncover the molecular mechanisms underlying drought tolerance in P. wilsonii. In our previous reports, multiple PwNAC genes were identified under drought stress based on transcriptome data analysis [30], but little is known about their function. In this study, we identified a novel NAC TF, PwNAC31, from the RNA-seq database.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, there have been many studies on the analysis of crop resistance to drought stress, but most of them have mainly focused on physiology and biochemistry [18][19][20] and transcriptomic analysis [21][22][23][24]. For instance, Guo et al [25] examined the transcriptomic changes induced by drought and salt stress in 8-week-old seedlings of Picea wilsonii via RNA-seq analysis. Previously, we conducted comparative RNA-seq transcriptome studies [26][27][28] and identified several candidate genes and metabolic pathways for drought tolerance in maize, including secondary metabolite biosynthesis related enzymes, such as probable Omethlytransfarase 2 (OMT2; Zm00001d019613) [28]; transcription factors (TF) such as MYBs, NAC and WRKYs; detoxification and stress responsive proteins including aquaporin PIP2-4 (Zm00001d017288), HSPs and GSTs [26][27][28].…”
Section: Introductionmentioning
confidence: 99%